Neuropsychiatric symptoms associated multimodal brain networks in Alzheimer's disease. Issue 1 (22nd August 2022) - Li, Kaicheng; Zeng, Qingze; Luo, Xiao; Qi, Shile; Xu, Xiaopei; Fu, Zening; Hong, Luwei; Liu, Xiaocao; Li, Zheyu; Fu, Yanv; Chen, Yanxing; Liu, Zhirong; et al.
Abstract: Concomitant neuropsychiatric symptoms (NPS) are associated with accelerated Alzheimer's disease (AD) progression. Identifying multimodal brain imaging patterns associated with NPS may help understand pathophysiology correlates AD. Based on the AD continuum, a supervised learning strategy was used to guide four‐way multimodal neuroimaging fusion (Amyloid, Tau, gray matter volume, brain function) by using NPS total score as the reference. Loadings of the identified multimodal patterns were compared across the AD continuum. Then, regression analyses were performed to investigate its predictability of longitudinal cognition performance. Furthermore, the fusion analysis was repeated in the four NPS subsyndromes. Here, an NPS‐associated pathological–structural–functional covaried pattern was observed in the frontal‐subcortical limbic circuit, occipital, and sensor‐motor region. Loading of this multimodal pattern showed a progressive increase with the development of AD. The pattern significantly correlates with multiple cognitive domains and could also predict longitudinal cognitive decline. Notably, repeated fusion analysis using subsyndromes as references identified similar patterns with some unique variations associated with different syndromes. Conclusively, NPS was associated with a multimodal imaging pattern involving complex neuropathologies, which could effectively predict longitudinal cognitive decline. These results highlight the possible neural substrate of NPS in AD, which may provide guidance for clinical management. Abstract : Neuropsychiatric symptoms (NPS)‐associated multimodal pattern spatially involves frontal‐subcortical limbic circuits, which significantly associated with cognitive performance and progression. Different frontal‐subcortical limbic circuit regions suffer different pathogenic mechanisms in Alzheimer's disease subjects concomitant with NPS. Subsyndrome‐specific patterns identified among neuropsychiatric subsyndromes.